2014
DOI: 10.1007/s00270-013-0826-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Delcath Systems’ Generation 2 (GEN 2) Melphalan Hemofiltration System in a Porcine Model of Percutaneous Hepatic Perfusion

Abstract: PurposeA new melphalan hemoperfusion filter (GEN 2) was evaluated in a simulated-use porcine model of percutaneous hepatic perfusion (PHP). The current study evaluated melphalan filtration efficiency, the transfilter pressure gradient, and the removal of specific blood products.Materials and MethodsA porcine PHP procedure using the GEN 2 filter was performed under Good Laboratory Practice conditions to model the 60-min clinical PHP procedure.ResultsThe mean filter efficiency for removing melphalan in six filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…The mean filtration rate in our study was lower than that obtained in in vivo, pre-clinical studies. In a study including 6 pigs treated with PHP with the first-generation filter, the filter extraction rate was 99% [ 10 ]. In our study, the mean efficiency dropped from 95.4% at T 10 to 77.5% at T end infusion , although the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean filtration rate in our study was lower than that obtained in in vivo, pre-clinical studies. In a study including 6 pigs treated with PHP with the first-generation filter, the filter extraction rate was 99% [ 10 ]. In our study, the mean efficiency dropped from 95.4% at T 10 to 77.5% at T end infusion , although the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mean efficiency dropped from 95.4% at T 10 to 77.5% at T end infusion , although the difference did not reach statistical significance. Pre-clinical studies have also shown that the filter efficiency decreases during the perfusion [ 10 ]. We hypothesise that the filter is more saturated at the end of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some fatalities were observed on this trial and each death lead to further safety maneuvers in the development of improved filters. [15,16] The authors concluded that the results of their phase III study demonstrate the efficacy of PHP-Mel. They report that the toxicity is significant but manageable in order to provide effective therapy for this select cohort of patients.…”
Section: Phase III Multicenter Trialmentioning
confidence: 96%
“…These filters are reported to have increased melphalan extraction efficiency. [15] In the portion of patients treated with the second generation filters, the toxicity was found to be milder and patients experienced a faster recovery. [14] Similar to other groups with experience in PHP, Vogl et al [14] concluded that PHP for non-resectable liver metastasis is a feasible treatment.…”
Section: Moffitt Cancer Center Experiencementioning
confidence: 99%